Możliwości interpretacyjne kategorii wstrętu na przykładzie popkulturowej figury zombie. Perspektywa edukacji estetycznej - Lisiecka, Alicja (Studia Edukacyjne, 2022)
The article is devoted to the analysis of the interpretive potential of disgust, examining the pop culture zombie figure. The analyses are conducted from the perspective of aesthetic education. The author focuses on such aspects of the zombie figure as: epidemic, impurity, concept of the Other, abjection, the body, and corporeality. The literature used in the analyses comes from various disciplines: psychology, philosophy, aesthetics, pedagogy, etc.